The Process of Assimilation-Accommodation in Solving the Problems of Proportion - Junarti Junarti; Ari Indriani; Istiqomah Istiqomah (International Conference on Science, Education, and Technology, 2021)
The purpose of this study was to describe the assimilation-accommodation process on a proportion topic. The descriptive qualitative approach was utilized to elucidate the assimilation-accommodation process. Data collection was accomplished using assessments administered to 13 students online and 7 students offline. The participants were chosen from a pool of twenty students based on their classification of procedural predictions of mathematical connection indicators. Six research subjects were selected from seven students who satisfied the expected indications of assimilation, accommodation, and assimilation-accommodation, with each category two students having the identical work. Additionally, data are gathered through tests and interviews that have been triangulated for source and method validity. The findings indicated the first two subjects demonstrate the assimilation process through the phases of proportion concept knowledge taught in primary school. This is shown by how the problem is solved, which begins with formulating the symbolic form proportion formula in variables. In proportion, the following two subjects demonstrate the accommodation process by converting their knowledge into different types of formula produced by assimilation groups, which is in the form of numbers. This is shown by how the problem is solved by immediately writing the answer into the proportion form without using another variable symbol. Meanwhile, the accommodation-assimilation process indicate a proclivity for modifying prior information by dividing proportion formula into different solution procedures from the assimilation and accommodation groups, i.e., in mixed form (some symbols and some numbers). The findings of this study indicate that the assimilation-accommodation process can aid in the acceleration of problem solutions in new materials.